Implementation of the Geometric Mean Multi-Attribute Utility Theory (G-MAUT) in Determining the Best Honorary Employees - Setiawansyah, Setiawansyah; Rahmanto, Yuri; Ulum, Faruk; Triyanto, Dedi (Jurnal Ilmiah Computer Science, 2025)
Determining the best honorary employees is a strategic step to appreciate performance, increase motivation, and encourage productivity in the work environment. This process is carried out by evaluating employees based on certain criteria. The main problem in determining the best honorary employees is the lack of objectivity and transparency in the assessment process, which often leads to dissatisfaction among employees. Judgments that rely solely on subjective perceptions without considering measurable quantitative data can result in unfair decisions. The purpose of applying the Geometric Mean Multi-Attribute Utility Theory (G-MAUT) method in determining the best honorary employees is to provide a more objective, transparent, and accurate evaluation framework in decision-making. This method not only supports a fairer selection process, but also encourages increased motivation and performance among honorary employees. The results of the calculation of the final utility value carried out using the G-MAUT method, the results of the evaluation of eight honorary employees showed their performance ratings comprehensively. Honorary Employee F has the highest utility value of 0.6399, making it the best honorarium employee among all available alternatives. Followed by Honorary Employee A who was ranked second with a utility value of 0.4685, and Honorary Employee D in third place with a value of 0.3947. These results provide a clear picture of the order of employees based on their performance in various criteria that have been assessed.